Pola Kuman dan Uji Kepekaan Antibiotik Pada Pasien Unit Luka Bakar RSUP Sanglah Periode 1 Januari 2016 - 1 Januari 2017 - I Wayan Jorden Junior; I Made Suka Adnyana; I Wayan Subawa; Vivi Paula Putri (DiscoverSys Inc., 2019)
Background: Burns are a skin injury or injury caused by thermal that causes morbidity or mortality in patients, due to either heat or radiation, electrical and chemical reactions. In burns can occur bacterial growth that will cause an infection, both gram-positive bacteria and gram-negative bacteria. Necessary antibiotics in the treatment of infection by bacteria on burns. The incidence of burns is increasing from year to year, but data in Indonesia that discuss about the number of infections in burns and the use of antibiotics is still small.Aim: The study aims to determine the pattern of germs and antibiotic sensitivity test in patient burn unit at Sanglah Denpasar Hospital period January 2016 - January 2017.Method: This research is a descriptive descriptive cross sectional study conducted at Sanglah Denpasar General Hospital (RSUP). Data obtained in the form of secondary data of medical record of patient period January 2016 - January 2017. Data were analyzed by using SPSS program.Result: The results showed that from 63 patients, found 51.0% gram positive and 49.0% gram negative. In the positive gram found 8 species of bacteria with the most bacteria that is Staphylococcus aureus 15.87% and Strep Î² Haemolyticus 15.87% and gram negative found 3 types of bacteria with the highest number Pseudomonas aeruginosa 30.16%.Conclusion: Antibiotics with the highest resistance were found Amoxicillin 85.7%, Amoxicillin / Sulbactam 81.2% and Ampicillin 87.5% while the highest sensitivity antibotics were Amikacin 82.3%, Meropenem 75.0% and Linezolid 85.7% both on gram negative and gram positive.